Possibility to Use Knowledge about the Contemporary E-consumer on the Tourist Services Market - Malgorzata MISNIAKIEWICZ; Jaroslaw PAWLIK (Communications of International Proceedings, 2021)
The progressive digitization of society, development of modern technologies, virtual and augmented reality, and further limitations related to the COVID-19 pandemic are factors that contribute to the dynamic virtualization of the purchasing behaviour of contemporary consumers. Their intensification in different areas of life can be observed, including the tourism and hospitality industry. The Internet is used to search for inspiration, trip offers, hotels, restaurants, and ideas of spending free time. Opinions and on line recommendations of the previous users are more and more influential when making a purchasing decision. Therefore, the aim of this paper is to analyse information about the contemporary e-consumer and to identify the possibilities of using this knowledge by current tourism and hotel industry. The paper specifies values important for e-consumers and kinds of personality traits they most often identify with. Their propensity to save and driving motives in this regard were determined. Moreover, the paper discusses the behaviour of e-consumers with relation to the opinions of the users of given products or services in the tourism industry and the use of new forms of direct marketing. The study contributes to significant managerial implications in developing tourism websites and advancing the service they provide.
Keywords: E-Commerce; Hospitality; E-Consumer Behaviour; Tour Operators Marketing.